Structural and functional characterization of a DARPin which inhibits Ras nucleotide exchange - Sandrine Guillard (Nature Portfolio, 2017)
Ras is mutated in many cancers, but so far no drug targeting Ras is in clinical use despite great efforts. Here the authors structurally and functionally characterize a DARPin that potently inhibits the nucleotide exchange of Ras, which might facilitate the development of Ras-targeted therapies.